Praktik Kerja Sama Bisnis Ayam Potong Perspektif Ekonomi Syari’ah Di Kecamatan Rajadesa - Badruzaman, Dudi (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The cooperation practice of meat-producing chicken business perspective shari?a economy in rajadesa district carried out by the both contracting parties. The result of the cooperation agreement was divided when gains obtained after the business was doing, but in practice did not accordance to the reality. The divison result was decided at the beginning that did not change. The formulation of the problem in this research, namely: (1) How is the cooperation practice of meat-producing chicken in Rajadesa District? (2) How is the cooperation practice of meat-producing chicken in Rajadesa District based on Musharaka contact?  The purpose of this research was to answer these problems. Based on the above issues, this type of research in this thesis was using qualitative research with descriptive approach. The data used in this research was the primary data. It was the sources of data obtained directly from meat-producing chicken business in kubangsari, Rajadesa District. The secondary data was acquired from the records, books, journals, and other issues related to the researcher analysis. Data collection techniques in this research were interview, observation and documentation. The data analysis used was phenomenology.